Etiology and Treatment of Developmental Stammering - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The etiology and treatment of developmental stammering in childhood (DS, also called idiopathic stammering or stuttering) are reviewed by a speech pathologist and psychologist at the University of Reading, UK.